Development of Low Frequency Vibration Method of Direct-Write Deposition Relevant to Layer Manufacturing Application - Widyanto, Susilo Adi; Tontowi, Alva Edy; Jamasri, Jamasri; Budi Rochardjo, Heru Santosa (Makara Journal of Technology, 2005)
The research of deposition process is the first step in development process of multi materials selective laser sintering. The deposition process enables to settle multi materials powder in horizontal formation on one layer. In this research we use low frequency (70 - 200Hz) to vibrate a hopper nozzle in which powder is settled. The research method consists of two steps, the first step is to determine flow-ability parameters and the second is to join flow ability parameter with other parameters such that the line width can be controlled. The results show that the line width depends on uniformity of particle size, particle size, frequency of vibration, deposition gap, particle shape and feed-rate of hopper-nozzle.